Influence of plant growth regulators on growth, seed yield, quality and economics of coriander (Coriandrum sativum L.) cv. Sudha - Sivaram, D S Reddy, V Yugandhar, P S S Reddy, G Thanuja (Journal of Spices and Aromatic Crops, 2016)
A field experiment was conducted to study the effect of plant growth regulators (PGRs) on growth, seed yield, quality and economics of coriander (Coriandrum sativum L.) cv. Sudha. The seven treatments included in the experiment are two concentrations each of GA3 (50 and 75 ppm), NAA (10 and 25 ppm), Cycocel (100 and 250 ppm) and control (water spray), as presoaking, foliar spray at 30 and 60 DAS. Among different PGRs applied, spray of 75 ppm GA3 resulted in significant maximum plant height. However, maximum number of primary branches and secondary branches plant-1, number of umbels plant-1, number of umbellets umbel-1, number of seeds umbel-1, seed yield and B:C ratio was maximum with 250 ppm Cycocel. Minimum number of days to 50% flowering and maturity and maximum carbohydrate content and protein content were noticed with 75 ppm GA3. Similarly, lowest moisture content in seeds was also observed with 75 ppm GA3, while, the essential oil content in seeds was maximum with 50 ppm GA3.